Pregnancy outcome in preterm premature rupture of membranes between 24 to 34 weeks of gestation - Venkatraman, Sujatha; Chaturvedula, Latha; Parija, Subhash Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Preterm premature rupture of membranes (PPROM) is spontaneous rupture of the fetal membranes before 37 completed weeks and before onset of labour which complicates 3-5% of all pregnancies. Studies regarding PPROM in very early gestation are lacking. The primary objective was to assess the maternal and perinatal outcome in preterm premature rupture of membranes and secondary objective was to assess the colonization of group B Streptococci (GBS) and Listeria monocytogenes in patients with PPROM. Methods: This prospective study was performed on 175 antenatal women with PPROM between 24 to 34 weeks of gestation. Results: Majority of women (54.2%) were between 32 to 34 weeks of gestation, 37% were between 28 to 32 weeks of gestation and 7.8% were between 24 to 28 weeks of gestation. About 22 % of women had cervicovaginal infections. The prevalence of group B Streptococci in the study group was 1.2% and no isolates of Listeria. The most common maternal morbidity was puerperal fever (11.4 %). Among newborn babies 87 (55 %) required neonatal intensive care unit (NICU) admission mainly for respiratory distress and prematurity. With each week of increase in gestational age, there is decrease in latency period by 22 hours and duration of NICU stay nearly by one day. Conclusions: From the present study it may be concluded that PPROM is associated with genitourinary infection, puerperal pyrexia and respiratory distress syndrome among neonates. The prevalence of group B Streptococci in antenatal women with PPROM is very low and no Listeria were isolated.